Structural equation modelling of relationships of personnel services and perceived principal supervision with academic achievement in secondary schools in Kwara State, Nigeria - Suleiman, Yusuf (2017)
The low performance of students in senior secondary schools‘ examinations is a serious concern for stakeholders in the education sector. This made them wonder if lack or inadequate school facilities could be responsible for it. Previous studies have established inconsistent findings on one or two dimensions (health and library) of students‘ personnel services may be linked to this low academic achievement. This showed that there was less attention on other aspects of the services. Effective supervision has been identified as an important factor that could influence academic achievement in school. Therefore, there is a need to investigate whether there are other factors in school that may contribute to students‘ low academic performance. As such, this study attempts to examine the impact of principal‘s supervision on the relationship between students‘ personnel services and academic achievement via a mixed methods approach. A quantitative approach, where survey design with 379 respondents (students) were used for the study, while a qualitative approach using an in-depth interview (20 principals) was employed to complement the findings of the quantitative data. Data collected was analyzed using descriptive and inferential analysis in the questionnaire data, while the interview data was analyzed thematically. Results indicate that four out of the five direct hypotheses formulated for the study were supported. Specifically, there is a relationship between library, guidance and counselling, extracurricular, health services and academic achievement. On the other hand, only two out of five of principal‘s supervision moderates these relationships. The interview findings reveal that the provision and supervision of these services is an important factor that influences academic achievement. Finally, this study demonstrates that the importance of principal‘s supervision cannot be ignored, as it is an essential factor for achieving students‘ academic success. Thus, this study has contributed to the body of knowledge practically, theoretically, and methodologically.